No Vehicle Means No Aid—A Paradigm Change for the Humanitarian Logistics Business Model - Hirschinger, Micha; Moser, Roger; Schaefers, Tobias; Hartmann, Evi (Thunderbird International Business Review, 2015)
The growing interest in humanitarian logistics is witnessed by an increasing focus of researchers and practitioners on that topic. Transportation in particular is emphasized as key to disaster relief. Despite its relevance, it suffers from a number of drawbacks creating inefficiencies and limited effectiveness of aid. This article describes a paradigm change for fleet management in humanitarian organizations based on access-based consumption. It further evaluates a case study among small-scale producers in rural India, showing their acceptance for sharing vehicles. The newly created business opportunities will increase income and contribute to poverty alleviation. Taking part in the proposed truck sharing system can release them from ownership responsibilities, increase vehicle utilization as well as improve vehicle availability respectively speed of aid from the perspective of humanitarian organizations. This article highlights the applicability of business models relying on the idea of access-based consumption to not yet considered research fields. Especially the transfer to rural areas of developing countries makes this article uniqu
Keywords: Access-based; Consumption; Humanitarian; Logistics; Sustainable; Development; Developing; Countries